PENGARUH METODE PEMBELAJARAN PROJECT BASED LEARNIN TERHADAP KEMAMPUAN KERJASAMA PADA ANAK KELOMPOK B DI KB ASSYARO MONTONG DAO - Maryati, Eni; Habibi, M.A. Muazar; Jaelani, Abdul Kadir; Rachmayani, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of project based learning methods on the ability of cooperation in children in group B at KB Assyaro Montong Dao. This study was conducted using a quasi-experiment with a non-equivalent control group design. The sample in this study was group B2 consisting of 15 children as the experimental group and group B1 consisting of 15 children as the control group. The data collection method used in this study was observation and tests used to collect data on children's cooperation abilities before and after treatment. The data obtained were analyzed with prerequisite tests, namely the normality test with the Kolmogorov-Smirnov test with a significance level of 5% (0.05) and continued with the homogeneity test using the Homogeneity of Variance test. Furthermore, the hypothesis test was carried out using the independent sample t-test. Based on the results of data analysis, it is known that the ability of children to cooperate with the hypothesis test at a significance level of 5% shows t count = 6.464> t table = 1.69913 and the sig value (2-tailed) is 0.001 <0.05, so the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This means that there is an influence of the project based learning method on the ability to cooperate in group B children at KB Assyaro Montong Dao.